GATA4 Is Required for Budding Morphogenesis of Posterior Foregut Endoderm in a Model of Human Stomach Development - DeLaForest, Ann; Quryshi, Afiya F.; Frolkis, Talia S.; Franklin, Olivia D.; Battle, Michele A. (Frontiers in Medicine, 2020)
Three-dimensional gastrointestinal organoid culture systems provide innovative and tractable models to investigate fundamental developmental biology questions using human cells. The goal of this study was to explore the role of the zinc-finger containing transcription factor GATA4 in gastric development using an organoid-based model of human stomach development. Given GATA4’s vital role in the developing mouse gastrointestinal tract, we hypothesized that GATA4 plays an essential role in human stomach development. We generated a human induced pluripotent stem cell (hiPSC) line stably expressing an shRNA targeted against GATA4 (G4KD-hiPSCs) and used an established protocol for the directed differentiation of hiPSCs into stomach organoids. This in-vitro model system, informed by studies in multiple non-human model systems, recapitulates the fundamental processes of stomach development, including foregut endoderm patterning, specification, and subsequent tissue morphogenesis and growth, to produce three-dimensional fundic or antral organoids containing functional gastric epithelial cell types. GATA4 protein was depleted by 70% in G4KD-hiPSC-derived definitive endoderm (DE) compared with control hiPSC-derived DE. We confirmed that GATA4 depletion did not disrupt hiPSC differentiation to DE. However, when G4KD-hiPSC-derived DE cells were directed to differentiate toward budding SOX2+, HNF1B+ posterior foregut spheroids, we observed a striking decrease in the emergence of cell aggregates, with little to no spheroid formation by GATA4-depleted hiPSCs. In contrast, control hiPSC-derived DE cells, expressing GATA4, formed aggregates and budded into spheroids as expected. These data support an essential role for GATA4 during the earliest stages of human stomach development.